The Health Literacy of Employees in Educational-Rehabilitation Centers Affiliated to The Welfare Organization - Mehnoosh Shahbazi; Zahra Mortazavi; Zahra Nazemi; Khadije Ezzati- Rastegar; Saideh-sadat Mortazavi (Mashhad University of Medical Sciences, 2021)
Background and Objective: Health literacy provides the capacity and basic understanding of health information and services for individuals to make health decisions. This study aimed to determine the health literacy of employees in educational-rehabilitation centers affiliated to the Welfare Organization of Hamadan province in 2019.   Materials and Methods: This cross-sectional study was conducted on 106 participations. Sampling was done by censuses method. Data was collected with the test of functional health literacy in adults (TOFHLA) and demographic questionnaire, and analyzed by, ANOVA, chi-squared tests via SPSS software version 21.   Results: The mean age of participants was 34.25± 8.19 years in females and 34.44± 8.60 years in males, and 90.57% were female, and 66.98% of them were married. The health literacy score was 65.90 ± 21.10, and 32.29% of females and40% of males were at an adequate level of health literacy. Level of health literacy was significantly different between participants with diffrent education level (P <0001), type of rehabilitation center (p = 0.001), specialized services of the center (P <0001), and gender.   Conclusion: The level of health literacy of more than half of the employees in the rehabilitation-educational centers affiliated with the welfare organization is inadequate and marginal. Due to the vulnerability of welfare clients, it is necessary to pay more attention to health literacy in health promotion programs in this organization.